Bahaya Social Engineering dalam Sosial Media - Sri Utami; Dina Afifah; Masduki Asbari (Yayasan Aya Sophia Indonesia, 2023)
The purpose of this research is to explain how the dangers of Social Engineering in using social media. In this study, a qualitative approach was used using the see note method, which was sourced from the Youtube channel (Diskusi Bersama Sabrang MDP) entitled